Social Justice Theory and Practice for Social Work Critical and Philosophical Perspectives - Watts, Lynelle; Hodgson, David (Springer Nature Singapore : Imprint: Springer, 2019)
This book offers a much-needed critical overview of the concept of social justice and its application in professional social work practice. Social justice has a rich conceptual genealogy in critical theory and political philosophy. For students, teachers and social workers concerned with empowerment, social change and human rights, this book provides a guide to the key ideas and thinkers, crucial historical developments and contemporary debates about social justice. It synthesises interdisciplinary knowledge and offers a new framework for practice, including a clear and practical exposition of four domains of skills and knowledge important for social justice informed social work. The book also contributes to social work pedagogy by offering a comprehensive set of learning outcomes that can be used to design curriculum, teaching and learning, and further research into social justice praxis. This book provides a range of philosophical and critical perspectives to support and inform social work professional knowledge and skills. In its tight knitting together of theory and practice this book links philosophical and moral principles with an understanding of how to engage with social justice in a way that is relevant to social work.